TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA GOLONGAN 1 (Studi Putusan Pengadilan Negeri Kabanjahe Nomor. 146/Pid.Sus/2020/Pn Kbj) - Emilia Fedika; Maria Ferba Editya S; Rayani Saragih (Journal Recht (JR), 2022)
The factors that influence the occurrence of criminal acts of narcotics abuse, to find out the application of material criminal law regarding the criminal act of narcotics abuse Group 1 based on the decision of the Kabanjahe District Court Number. 146/Pid.Sus/2020/Pn Kbj and to find out the judge's considerations in imposing criminal sanctions against the criminal act of Narcotics abuse Group 1 based on the decision of the Kabanjahe District Court Number. 146/Pid.Sus/2020/Pn Kbj. The data collection technique used in this study was by means of a study of literature and analyzed qualitatively. The results achieved in this study indicate that, the factors that influence the occurrence of narcotics abuse crimes committed by the defendant can be seen by the presence of internal factors and external factors, the application of material criminal law by the judge to the criminal act of Narcotics Abuse of Category I type of methamphetamine in the decision Number. 146/Pid.Sus/2020/Pn Kbj is correct where the public prosecutor uses Article 114 paragraph (1) of the Law of the Republic of Indonesia Number 35 of 2009 concerning Narcotics in conjunction with Article 132 paragraph (1), and Article 112 paragraph (1) of the Law -Law of the Republic of Indonesia Number 35 of 2009 concerning Narcotics in conjunction with Article 132 Paragraph (1) of the Law of the Republic of Indonesia Number 35 of 2009 concerning Narcotics and legal considerations by judges on the criminal act of Narcotics Abuse of Category I in imposing a sentence is correct because the Judge in case Number I . 146/Pid.Sus/2020/Pn Kbj imposed a sentence based on the testimony of witnesses, the testimony of the defendant, and evidence